Does advanced maternal age influence obstetric outcome: a study in a tertiary care centre - C. V., Jose; George, Lissiamma; Sukumaran, Sunitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Advanced maternal age defined as age 35 years and older at estimated date of delivery has become increasingly common in last two to three decades. The International Federation of Gynaecology and Obstetrics in 1958 recommended that all women going through their first pregnancy over the age of 35 years should be considered high risk for pregnancy and included in this category 1. Methods: A one-year prospective observational study conducted in a tertiary care hospital after institutional ethical clearance. All 165 women above 35yrs who delivered during this period were taken as Cohort 1. Same number of women aged between 20 and 34 years were randomly selected as comparison group (Cohort 2). Both the groups were compared in terms of preexisting medical disorders, obstetrical morbidities, antenatal complications, intrapartum complications. Results: Older and younger women had similar antenatal booking, occupational and socioeconomic status. The main reason for pregnancy at advanced age group was late marriage. The risk of chronic hypertension, gestational diabetes mellitus, pre-existing medical disorders were higher in advanced maternal age. Conclusions: Increasing maternal age is associated with elevated risks for pregnancy complications. They are at high risk for gestational diabetes, cesarean section and to have low birth weight babies. Since these women are at higher risk of complications, they should be advised to adhere to frequent antenatal visits and close supervision.